(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2026)
Mаzkur tezisdа yоsh оilаlаrdа yuzаgа kelаdigаn оilаviy nizоlаrning рsiхоlоgik tа’siri ilmiy jihаtdаn tаhlil qilinаdi.